Create your own dream feathers - Holt, Peggy, 1946- (American Quilter's Society, 2012)
"Continuous line designs to create quilting patterns-feathers, butterflies, hearts, paisleys, and more. Three concepts underlie this approach to free-motion quilting. Designs work for longarm, midarm, or domestic quilting, and hand quilting"--